THE INFLUENCE OF COMMON CARP MEAT (Cyprinus carpio) DIET ON BRAIN INDEX AND THE EXPRESSION OF GENE NR2B OF SWISS WEBSTER MICE CEREBRUM - Philips Onggowidjaja; M. Nurhalim Shahib (Universitas Kristen Maranatha, 2015)
This research was to evaluate the influence of common carp meat diet on brain index and gene NR2B expression of Swiss Webster mice cerebrum. The gene expression and performance of ion Ca2+ channel in neuron are influenced by Glycine and Glutamic Acid, which present in relatively high quantities in common carp meat. Eighteen male mice were divided into 3 diet groups, the standard pellet, 120 mg and 480 mg common carp meat/day. The brain index differences among groups were analyzed using ANOVA test (p≤0,05) and LSD. The total RNA of 5 mg mouse cerebrum was isolated, followed by RT-PCR; the DNA quantities were predicted using Geldoc instrument, then were analyzed using ANOVA test (p≤0,05). The 120 mg diet group brain index did not show difference (p=0,284) against the standard diet group, while the 480 mg diet group showed the increase compared to the standard (p=0,034) and 120 mg diet groups (p=0,004). No DNA quantity differences of all groups (p=0,195). It was concluded, the 480 mg common carp meat/ day diet increased the brain index of Swiss Webster mice, while the 120 mg and 480 mg common carp/day diets did not influence the gene NR2B expression of Swiss Webster mice cerebrum. Keywords : brain index, gene NR2B expression, common carp meat diet